Immune status, well-being and gut microbiota in military supplemented with synbiotic ice cream and submitted to field training: a randomised clinical trial. Issue 12 (28th December 2021) - Valle, Maria C. P. R.; Vieira, Isabel A.; Fino, Luciana C.; Gallina, Darlila A.; Esteves, Andrea M.; da Cunha, Diogo T.; Cabral, Lucélia; Benatti, Fabiana B.; Marostica Junior, Mario R.; Batista, Ângela G.; Santos, Rosangela; Pastore, Glaucia M.; et al.
Abstract: Strenuous physical activity, sleep deprivation and psychological stress are common features of military field training. The present study aimed to evaluate the effects of supplementation with a synbiotic ice cream on salivary IgA, gastrointestinal symptoms, well-being indicators and gut microbiota in young military participants undergoing field training. Sixty-five military completed the study: one group was supplemented for 30 d with synbiotic ice cream containing: 2·1 × 10 8 CFU/g for Lactobacillus acidophilus LA-5 and 2·7 × 10 9 CFU/g for Bifidobacterium animalis BB-12 and 2·3 g of inulin in the 60 g of ice cream at manufacture, and the other with a placebo ice cream. Volunteers were evaluated at pre-supplementation (baseline), post-supplementation and after a 5-d military training. Bifidobacterium and Lactobacillus genera were measured in stool samples and both showed a higher differential abundance post-supplementation and training. Salivary IgA and gastrointestinal symptoms decreased at post-training in both groups ( P < 0·05; main effect of time); however, supplementation with synbiotic did not mitigate this effect. Tenseness and sleepiness were decreased in the synbiotic-treated group, but not in the placebo group at post-military training ( P = 0·01 and 0·009, respectively; group × time effect). The other well-being indicators were not affected by the synbiotic supplementation. In conclusion, 30 d of synbiotic ice cream supplementation containing inulin, L. acidophilus LA-5 and B. animalis BB-12 favourably modulated gut microbiota and improved tenseness and sleepiness in healthy young military undergoing a 5-d field training. These improvements may be relevant to this population as they may influence the decision-making process in an environment of high physical and psychological stress.